Remote control using telephone / Sufian Mohamad and Muhd Amirulfikri Abu Hashim - Mohamad, Sufian; Abu Hashim, Muhd Amirulfikri Abu Hashim (2005)
Remote control using telephone is a device that enables switching ‘on’ and ‘off of appliances through telephone lines. It means that we can switch appliances in any distance from our home. The purpose of this project is to enable the user to switch appliances although they are not in home. It can be done by dialing their home phone number to switch off the appliances without returning back to their home. Appliances can be selected by pressing pre-programmed button